The Use of Military Profiles in Romance Fraud Schemes - Cross, Cassandra (Victims & offenders, 2021)
Romance fraud occurs when offenders use the guise of a genuine relationship to defraud a victim, typically via online communications. Research has focused on the general structure of romance frauds, but few scholars have considered the potential link between victimization and specific narratives employed by offenders. This article explores the reported romance fraud victimizations of a group of Australians and explores similarities and differences in how a military narrative is involved compared to other genres. Limited differences were observed between those frauds using military narratives, highlighting the need for broader consideration of fraud prevention and disruption measures.